Creativity and Personality Styles: An approach to creative profiles in university students - Limiñana Gras, Rosa María; Corbalán Berna, Javier; Sánchez López, María Pilar (Anales de Psicología / Annals of Psychology, 2010)
The goal of this study is to analyse the presence of this diver-gent thinking in university students and its connection to personality styles. Sample is made up of 86 Speech Therapy and Psychology under-graduate students. The average age is 22, out of which 15.1% are male and 84.9% are female. Assessment of creativity has been achieved by using the CREA Test. (Corbalán, Martínez, Donolo, Alonso, Tejerina y Limiñana, 2003). CREA test is intended at appreciating creative intelligence by means of an indicator of question-raising within a theoretical context of problem seeking and solving. Personality styles were evaluated by using MIPS (Millon, 2001), which offers a method to measure personality styles, or-ganized into three main dimensions: motivational goals, cognitive modes and interpersonal behaviours. Results illustrate differential creative profiles according to their creative production, showing significant relations be-tween some of the personality variables studied and creativity. These, in turn, could provide relevant information about creative behaviours in these university students.